Determining the Operational Performance in Supply Chain with Moderating Role of Information Quality: A case of Thai Textile Industry - Waleerak Sittisom; Witthaya Mekhum (International Journal of Supply Chain Management, 2020)
The prime objective of the current research is to determine the operational performance of textile units of Thailand. The study was conducted on the Thai textile manufacturers as this industry is one of important and backbone for economy. The study aims to determine the operational performance predictors and investigated the relationship between technology integration and logistics integration. The information possesses the central importance in management of supply chain and play vital role in supply chain activities as decision making based on information quality and accuracy. Inaccurate information will mislead the firm to take inappropriate decision in highly competitive environment. The study examined the moderating role of information quality and found interesting results that technology and logistics integration positively significantly influence the operational performance. The moderating effect was observed in technology integration and operational performance but no moderation effect was found between logistics integration and operational performance.